Energy Transition and Social Justice : Examining the Impact of Renewable Energy Supply Chain - Lehtonen, Tommi; Shakeel, Shah Rukh (Springer, 2025)
The scholarly discussion on renewable energy technology development has primarily focused on technological advancements and their integration into global energy systems. The supply chain’s role in carrying out technology development processes has received little attention. Exploring renewable energy development from a life cycle perspective reveals implications for social justice that transcend mere technological development. In terms of social justice, the biggest challenge in the energy transition is fairly distributing benefits and expenses to various groups of people across the renewable energy supply chain. The negative environmental impacts of energy production and consumption are often borne by marginalised communities. Therefore, it is crucial to ensure that the public, understood broadly, has a say in how the transition is planned and implemented. This means ensuring that there is public participation in decision-making processes, that communities are consulted about proposed energy transition projects, and that there is transparency in the decision-making process.
Keywords: energy transition; renewable energy; supply chain; lifecycle; supply chains; social justice; fi=Markkinointi|en=Marketing|; fi=Viestintätieteet|en=Communication Studies|